Microalgal growth, nitrogen uptake and storage, and dissolved oxygen production in a polyculture based-open pond fed with municipal wastewater in northern Sweden. (August 2021) - Lage, Sandra; Toffolo, Andrea; Gentili, Francesco G.
Abstract: Microalgal-based wastewater treatment and CO2 sequestration from flue gases with subsequent biomass production represent a low-cost, eco-friendly, and effective procedure of removing nutrients and other pollutants from wastewater and assists in the decrease of greenhouse gas emissions. Thus, it supports a circular economy model. This is based on the ability of microalgae to utilise inorganic nutrients, mainly nitrogen and phosphorous, as well as organic and inorganic carbon, for their growth, and simultaneously reduce these substances in the water. However, the production of microalgae biomass under outdoor cultivation is dependent on several abiotic and biotic factors, which impact its profitability and sustainability. Thus, this study's goal was to evaluate the factors affecting the production of microalgae biomass on pilot-scale open raceway ponds under Northern Sweden's summer conditions with the help of a mathematical model. For this purpose, a microalgae consortium and a monoculture of Chlorella vulgaris were used to inoculate outdoor open raceway ponds. In line with the literature, higher biomass concentrations and nutrient removals were observed in ponds inoculated with the microalgae consortium. Our model, based on Droop's concept of macronutrient quotas inside the cell, corresponded well to the experimental data and, thus, can successfully be applied to predict biomass production, nitrogen uptake and storage, and dissolved oxygen production in microalgae consortia. Graphical abstract: Image 1 Highlights: Nordic microalgae strains treated wastewater and sequestered CO2 from flue gases. Microalgae consortium outcompeted C. vulgaris monoculture in outdoor open ponds. Microalgae consortium had higher biomass concentration and PO4 removal than monoculture. Mathematical model on microalgae growth, N uptake/storage, and O2 generation was made. Model simulated specific traits of microalgal behavior in complex growth conditions.